(untitled) (Journal Of Educational and Psychological Researches, 2017)
The objective of this research is to analyze the content of science textbook at the elementary level, according to the dimensions of sustainable development for the academic year (2015-2016). To achieve this goal has been to build a list with dimensions of sustainable development to be included in science textbooks in primary school, after seeing the collection of literature and research and studies, as has been reached to the list of the dimensions of the three sustainable development and social, economic and environmental in the initial image consisted of (63) the issue of sub-divided the three-dimensional, the menu and offered a group of arbitrators and specialists in curriculum and teaching methods, and thus the menu consisted in its final form (55) sub-issue. Then analyzed the researcher content of science textbooks in the elementary stage in the light of the list that has been built, and included a content analysis (155) page, and adopted the idea and unit for recording and repetition unit of the census, have been certified for analysis by a random sample of it presented to the arbitrators was carried out and all of them the validity of the analysis, and the use of Holsti equation has been the stability analysis account agreement with analysts outside and with the researcher herself, and the most important findings of the researcher’s book Science for second grade primary in second place came by (32.48%) of (55) again, . In light of the search results researcher recommended a number of recommendations including: Attention sub-neglected issues and work to be included in science textbooks for the primary stage. The researcher has proposed an update to this study several proposals, including: 1. The need for a teacher’s guide includes dimensions of sustainable development, which should seek to reinforce the students